The interplay between trade unions and the social security system in an aging economy - Max Friese (Universität Rostock, Institut für Volkswirtschaftslehre, 2019)
This paper investigates how demographic change affects the financial sustainability of a defined benefit pay-as-you-go social security system in an environment with collective bargaining on the labor market. Temporary equilibrium analysis shows that the contribution rate decreases, if the old-age dependency ratio rises. The government balances the social security budget by aiming indirectly at a higher level of employment. In the intertemporal equilibrium the opposite applies. The government increases the contribution rate due to additional effects of demographic change on capital accumulation and labor demand. In contrast to a perfect labor market scenario, the imposed financing burden from an aging society is overcompensated by favorable labor market effects on the social security budget.
More recent version: http://hdl.handle.net/10419/203152
Keywords: E24; H55; J11; J51; 330; demographic change; PAYG pension; social security; trade union; collective bargaining; unemployment